New approach to assessment of railway vehicle dynamical response in the course of passing over turnout - Zelenka, Jaromír; Hába, Aleš; Kohout, Martin (Ústav termomechaniky AV ČR, v. v. i., 2016)
In the course of a vehicle passing over a turnout, a significantly difference of dynamical response appears in vertical direction. Although a frog is the most loaded part of each turnout, a switch area is equally important part of a turnout from this point of view; so called suspended support of the switch area is tested at new turnout structures. The methodology for determination of the equivalent loading of a turnout frog in the course of a vehicle passing has been developed to evaluation of the frog loading. A vertical acceleration measured on the wheelset axle box of a vehicle passing over the frog is an input parameter for the calculation of the equivalent loading. Assessment of a vehicle dynamical response during passing over the suspended part in the switch area is also based on the vertical dynamical response measurement detected by acceleration sensors located on the wheelset axle box but this response is evaluated by statistical methods. Actually in cooperation with a turnout producer and one of the train operators, the turnouts of several types and in different operational condition are monitored since 2014 with application of the mentioned methodology. The reference vehicle for the monitoring of selected turnouts is an electric locomotive of axle load 22 t. The verification of optimized design of some turnouts in terms of loading of their parts is the main purpose of this research.
Nové přístupy k hodnocení dynamické odezvy kolejového vozidla při průjezdu výhybkou
Keywords: turnout; frog; railway vehicle; acceleration; measurement; výhybka; srdcovka; kolejové vozidlo; zrychlení; měření